Balinese Ethnomathematics in Numeracy Education: Culturally-Inspired Questions for Middle School Students - Puspadewi, Kadek Rahayu; Atmaja, I Made Dharma; Noviyanti, Putu Ledyari (Jurnal Pedagogi dan Pembelajaran, 2025)
The Minimum Competency Assessment (AKM) emphasizes numeracy as a vital skill for lifelong learning; however, AKM questions often lack cultural relevance, limiting students’ engagement and understanding. To address this issue, this study aims to develop numeracy questions based on Balinese ethnomathematics aligned with AKM by integrating local cultural contexts to make mathematical concepts more meaningful. This research employed a Research and Development (R&D) approach using the ADDIE model, involving eighth-grade junior high school students selected through purposive random sampling. Data were collected through questionnaires, tests, and expert evaluations, then analyzed quantitatively to assess the validity, practicality, and effectiveness of the questions. The results show that these ethnomathematics-based questions possess very high validity, practicality, and effectiveness, while also meeting the cognitive demands of AKM and enhancing student engagement. By integrating Balinese cultural elements such as traditional practices and local contexts, these questions help students connect abstract mathematical concepts with real-life applications. This study demonstrates the potential of culturally-based assessments to improve mathematical understanding and foster cultural pride, offering a framework for broader application in various educational contexts to promote more inclusive and meaningful learning.